Evaluation of nurses Attitudes Toward Medical Waste Management - Hussein hweid shukheer; Ghazwan Abdul Hussein Al-Abedi (Kerbala Journal of Nursing and Health Sciences., 2026)
Background: Medical waste puts nurses at a greater risk than others. Nurses visit the ward more than anyone which increases their chance of being exposed to hazards. It is important that they ensure the rest of the team and the community are not at risk of waste matters. The attitudes of nurses toward medical waste management are crucial for ensuring effective waste segregation, handling, and disposal practices. Positive attitudes can enhance compliance with established protocols, while negative perceptions may lead to unsafe practices, increasing the likelihood of infections and environmental contamination. Thus, the main objective of this study is to assess the level of nurse’s attitudes towards medical waste management and to find out the relationship between nurses’ attitudes and key sociodemographic characteristics such as age, sex, qualifications in nursing, years of experience, attending training courses and department they work in. Methods: A descriptive cross-sectional design was employed; 318 nurses were taken from various departments. Data were collected using a specially developed questionnaire encompassing demographic characteristics and attitudes toward medical waste management. Results: The findings revealed more than half of the sample %59.8 have a moderate level of attitudes towards medical waste management in the hospital under study. The results showed a statistically significant relationship between the sample's attitudes and their educational level, years of experience, and participation in training courses, respectively, at a significance level of 0.05%. Conclusion: The study highlights the critical role of nurses in effective waste management and underscores the need for targeted training programs to enhance compliance and safety practices.